Advances in global leadership. vol. 15 - Osland, Joyce; Mendenhall, Mark E., 1956-; Reiche, B. Sebastian; Maznevski, Martha L. (Advances in global leadership ;, 2023)
Advances in Global Leadership collects insights from leading scholars and practitioners and fresh ideas from promising newcomers to the field. In addition to traditional research, Volume 15 focuses on power and global leadership, an under-researched topic in the field of global leadership. This volume features: * An insightful, comprehensive literature review of power and global leadership. * Two ground-breaking research articles on factors that influence global power and change. * The editors' analysis of the field of power in global leadership and suggested future directions. * A comparison of the 2015-2020 global leadership publication patterns with a prior literature review to map the field's growth. * A cognitive approach to understanding global leadership effectiveness, featuring a conceptual model of trigger events in intercultural sensemaking. * Interviews with two luminaries in the field of global leadership. * An academic-practitioner collaboration of a popular Danish global leadership development training program that is available to the public. * Reflections by recent Emerald Literati Award Winners who made the most outstanding contributions to the field of global leadership in past volumes of Advances in Global Leadership. Given its multidisciplinary focus, this book is a must-read for scholars from a diverse set of scholarly fields and practitioners with a diverse set of global leadership roles. The Advances in Global Leadership series, with its finger firmly on the pulse of this exciting field, is an indispensable compendium of knowledge on global leadership.